2004
DOI: 10.1161/01.cir.0000150391.38660.9b
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Abnormalities in Glucose and Energy Metabolism and Coordinated Changes in Levels of Adiponectin, Cytokines, and Adhesion Molecules in Subjects With Metabolic Syndrome

Abstract: Background-Detailed metabolic defects in glucose and energy metabolism and abnormalities in a variety of cardiovascular risk factors are largely unknown in subjects with the metabolic syndrome. Methods and Results-We characterized the metabolic syndrome in 119 nondiabetic offspring of diabetic probands.Cardiovascular risk factors, including cytokines and adhesion molecules, were measured. Insulin sensitivity was assessed by the euglycemic hyperinsulinemic clamp and indirect calorimetry; intra-abdominal fat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
146
1
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(174 citation statements)
references
References 34 publications
(43 reference statements)
16
146
1
11
Order By: Relevance
“…29 Serum level of hsCRP, a marker of systemic inflammation, was more strongly related with MeS than other inflammatory biomarkers in regard not only to the number of components but also to their clustering, in agreement with previous reports in general population. 34,35 However, another study did not found significant relation between hsCRP and incidence of MeS in HD patients, may be due to lower sample size. 3 Serum level of hsCRP was significantly positively correlated with FPG and HbA1c, and negatively with HDL-C levels.…”
Section: Discussionmentioning
confidence: 93%
“…29 Serum level of hsCRP, a marker of systemic inflammation, was more strongly related with MeS than other inflammatory biomarkers in regard not only to the number of components but also to their clustering, in agreement with previous reports in general population. 34,35 However, another study did not found significant relation between hsCRP and incidence of MeS in HD patients, may be due to lower sample size. 3 Serum level of hsCRP was significantly positively correlated with FPG and HbA1c, and negatively with HDL-C levels.…”
Section: Discussionmentioning
confidence: 93%
“…First, an IVGTT was performed to determine the first-phase insulin secretion capacity [18] as previously described [16]. Immediately after an IVGTT, the degree of insulin resistance was evaluated by the euglycaemic clamp technique [19].…”
Section: Methodsmentioning
confidence: 99%
“…Genetically the Finnish population is relatively homogeneous, originating mainly from southern (European) and eastern (Asian) immigration about 2,000 years ago [15]. The study group consisted of 158 non-diabetic offspring of patients with type 2 diabetes from our ongoing study [16]. Patients with type 2 diabetes were randomly selected from patients living in the Kuopio University Hospital region (population of 250,000).…”
Section: Study Imentioning
confidence: 99%
“…Cross-sectional studies link decreased adiponectin levels with several metabolic traits, including insulin resistance, dyslipidemia, and the metabolic syndrome [2,4,5]. Moreover, low levels of adiponectin predict future development of diabetes [6], cardiovascular disease [7] and obesity-associated malignancies [8,9].…”
Section: Brief Communication (Original)mentioning
confidence: 99%